Innovative Elastography Measuring Cap for Ex Vivo Liver Condition Assessment: Numerical and Preclinical Studies in a Porcine Model - Dariusz Pyka; Agnieszka Noszczyk-Nowak; Karina Krawiec; Tomasz Świetlik; Krzysztof J. Opieliński (Livers)
The authors of this study focused their research on developing cap geometries for the FibroScan® elastograph (FibroScan, EchoSens, Paris, France) measuring head aimed at a non-invasive assessment of liver condition for transplantation using a pig animal model. Numerical models were created to simulate the propagation of a mechanical wave through a biological medium induced by the FibroScan® elastograph measuring head. The designed caps were intended to replicate the skin–muscle–rib–liver structures to minimize the risk of damage caused by mechanical wave excitation when directly applied to liver tissue. The construction process of numerical models for the liver and surrounding tissues is presented, along with simulations reflecting the mechanical and acoustic properties of the wave propagation process. The results obtained from in vivo measurements on pigs were validated through a numerical analysis, confirming a high level of agreement between the test results and the numerical model.